The Changing Politics of Gender Equality
XIII, 223 p.
Keywords: This comprehensive collection brings together key academics, activists and practitioners to review the changing politics of the 'project' of gender equality. It gives account of the evolution of gender equality policies and practice at different levels of governance in Britain over the past three decades. Thinking and work around equal opportunities have been fundamentally shaped by changing political conditions. The contributors review past policies and practices before moving on to explore the opportunities and challenges for the future.